10x-7=3x+7

Simple and best practice solution for 10x-7=3x+7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 10x-7=3x+7 equation:


Simplifying
10x + -7 = 3x + 7

Reorder the terms:
-7 + 10x = 3x + 7

Reorder the terms:
-7 + 10x = 7 + 3x

Solving
-7 + 10x = 7 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
-7 + 10x + -3x = 7 + 3x + -3x

Combine like terms: 10x + -3x = 7x
-7 + 7x = 7 + 3x + -3x

Combine like terms: 3x + -3x = 0
-7 + 7x = 7 + 0
-7 + 7x = 7

Add '7' to each side of the equation.
-7 + 7 + 7x = 7 + 7

Combine like terms: -7 + 7 = 0
0 + 7x = 7 + 7
7x = 7 + 7

Combine like terms: 7 + 7 = 14
7x = 14

Divide each side by '7'.
x = 2

Simplifying
x = 2

See similar equations:

| 7x^2+57x+42=7+3x | | 6-24x+14+35x=53 | | 10X^2-2X+8=0 | | 7x^2+57x+42=7 | | 6x-3x=15+4x | | 5x-1+3x=9 | | 6/7x2/5 | | a^2-13a=-12-6a | | 6a^2-13a+6a=-12 | | 2x+5-3x+1=0 | | 3/8*10x | | 4log(4x+5)=-2 | | 5x-1-3=2 | | 3b-4-3b/2 | | 9x+4=10x+3 | | Log[4](3X)=3 | | 8(4y)-9(y)+1=0 | | -25=2v-7 | | 7=-7(v+2) | | 5x+5+2x-2=-4 | | 64/8/2 | | (8d^5)/4d^-3 | | 38=3u-10 | | 2a=-(1-a) | | 10x+2=6x+42 | | 6X^3+60X^2+96X-160=0 | | -6x=24+18x | | 5w+9=54 | | 5x+1+2x-1=-4 | | 7(x+6)-9(9x-5)=15 | | 9(x+2)-2(x-8)=14 | | lnx=sqrt(8-lnx^2) |

Equations solver categories